2003
DOI: 10.1007/s10103-003-0274-6
|View full text |Cite
|
Sign up to set email alerts
|

Transmeatal cochlear laser (TCL) treatment of cochlear dysfunction: A feasibility study for chronic tinnitus

Abstract: Low-level-laser-therapy (LLLT) targeting the inner ear has been discussed as a therapeutic procedure for cochlear dysfunction such as chronic cochlear tinnitus or sensorineural hearing loss. Former studies demonstrate dose-dependent biological and physiological effects of LLLT such as enhanced recovery of peripheral nerve injuries, which could be of therapeutic interest in cochlear dysfunction. To date, in patients with chronic tinnitus mastoidal and transmeatal irradiation has been performed without systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
2
28
1
3
Order By: Relevance
“…In contrast to the findings of Nakashima et al, 18 Mirz et al, 19 and Teggi et al, 20 we found significant differences for subjective tests consisting of VAS for loudness, LMT, TQ and THI pre-to post-treatment. Consistent with Okhovat et al, 21 Tauber et al, 10 Cuda and De Caria, 14 Hahn et al 24 and Salahaldin et al, 16 an improvement in VAS, THI and reduction in loudness were reported pre-to post-LLLT in subjective descriptions of tinnitus. The efficacy of LLLT for tinnitus suppression according to subjective evaluations has been reported from 0% to 90% in different studies.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In contrast to the findings of Nakashima et al, 18 Mirz et al, 19 and Teggi et al, 20 we found significant differences for subjective tests consisting of VAS for loudness, LMT, TQ and THI pre-to post-treatment. Consistent with Okhovat et al, 21 Tauber et al, 10 Cuda and De Caria, 14 Hahn et al 24 and Salahaldin et al, 16 an improvement in VAS, THI and reduction in loudness were reported pre-to post-LLLT in subjective descriptions of tinnitus. The efficacy of LLLT for tinnitus suppression according to subjective evaluations has been reported from 0% to 90% in different studies.…”
Section: Discussionsupporting
confidence: 62%
“…It has been suggested to be effective in treatment of peripheral and central nervous system injuries, musculoskeletal injuries, Buerger disease and sympathetic nervous system dysfunction. [8][9][10] LLL is also used to treat chronic impaired hearing, sudden sensorineural hearing impairment, 11 Meniere disease and some other balance disorders. 12 It has also been reported to decrease tinnitus loudness and annoyance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tauber et al [2003] described changes in tinnitus loudness and matching. After a follow-up period of 6 months, tinnitus loudness was attenuated in 13 of 35 irradiated patients, while 2 of 35 patients reported their tinnitus as totally absent.…”
Section: Introductionmentioning
confidence: 99%
“…In his review, Dobie (2004a) reported no beneficial effect from any of these procedures. A subsequent exploratory study used low-powered laser technology (Tauber, Schorn, Beyer, & Baumgartner, 2003) that involved highly defined dose and positioning within the ear canal. Outcomes suggested that this refinement of the laser procedure may have beneficial value, meriting more systematic investigation.…”
Section: Acoustic-physical Treatments: Review Of Evidencementioning
confidence: 99%